Design of robust centralized PSS based on WAMS considering system and signal transmission delay uncertainties - Saejia, Mongkol; Ngamroo, Issarachai (My University, 2010)
It is well known that the time delay due to the wide-area phasor measurement unit (PMU) as well as various system operations may deteriorate the stabilizing effect of wide area monitoring system (WAMS). To overcome this problem, this paper proposes the design of robust centralized power system stabilizer (PSS) for wide area stabilization taking uncertainties due to system operations and signal transmission delay into account. The uncertainties due to system operations and time delay are represented by the inverse input and output multiplicative model. The structure of centralized PSS controller is the practical second order lead/lag compensator. To automatically tune the control parameter, the optimization problem based on the enhancement of damping performance and system robust stability margin is achieved by particle swarm optimization. Simulation studies in the two-area four-machine interconnected power system confirm that the proposed robust PSS centralized controller is superior to the conventional PPS in terms of robustness against system and time delay uncertainties.
Keywords: Phasor measurement unit; Robust control; System uncertainly; Wide area measurement system (WAMS)